Prospective study of maturation and injury in elite handball academy. Could `maturational status` be a risk factor for injury incidence in different handball team categories? - Mónaco, M.; Lopez, F. S.; Rincón, J. A. G.; Ronsano, J. B. M.; Toda, L. I.; Rodas, G. (Apunts Sports Medicine, 2024)
The objective of this study is to describe the relationship between injury incidence (IL) and maturity in male elite handball's player (HbP). Prospective study during two seasons, evaluating the sports injuries, maturity status and exposure time in hours in 133 young handball's players, under the UEFA methodology model for epidemiological studies. We discuss the maturity stage with different parameters, the Tanner's stage, puberty stages, peak high velocity, testicular volume, and the bone age. Finally, 190 injuries for a total of 34.222 h of exposure were registered.